Assessment of solar access in urban environment: The case of the renewal of a city block in Espinho, Portugal. Issue 7 (November 2016) - Marques, Bruno; Corvacho, Helena; Brandão Alves, Fernando
The research project carried out aimed to establish guidelines for urban design, especially adjusted to specific climatic conditions and to local design practice. With the aid of a simulation program, Townscope III, several urban scenarios were characterized in what concerns solar access. Some results are presented for the specific case of a block in Espinho. Four different building models were tested. Solar access was evaluated and its repercussion on heating and cooling energy needs of the buildings was estimated. A virtual scenario with an increase of the density of the urban surrounding area was also assessed.